Novel TRPV1 Channel Agonists With Faster and More Potent Analgesic Properties Than Capsaicin - Duarte, Yorley; Cáceres, Javier; Sepúlveda, Romina V.; Arriagada, Diego; Olivares, Pedro; Díaz-Franulic, Ignacio; Stehberg, Jimmy; González-Nilo, Fernando (Frontiers in Pharmacology, 2020)
The Transient receptor potential vanilloid 1 (TRPV1) ion channel is a member of the family of Transient Receptor Potential (TRP) channels that acts as a molecular detector of noxious signals in primary sensory neurons. Activated by capsaicin, heat, voltage, and protons, it is also well known for its desensitization, which led to the medical use of topically applied TRPV1 agonist capsaicin for its long-lasting analgesic effects. Here we report three novel small molecules, which were identified using a Structure-Based Virtual Screening for TRPV1 from the ZINC database. The three compounds with vanilloid scaffold and a linker amide or ester type were tested using electrophysiological assays, which confirmed their capsaicin-like activity. Von frey filaments were used to measure the analgesic effects of the compounds applied topically on tactile allodynia induced by intra-plantar carrageenan. All compounds had anti-nociceptive activity, but two of them showed faster and longer lasting analgesic effects than capsaicin.